A Combined Rock Magnetic and Meteorological Investigation of the Precipitation Boundary Across the Tibetan Plateau. Issue 18 (12th September 2021) - Ning, Wen‐Xiao; Zan, Jin‐Bo; Yang, Sheng‐Li; Fang, Xiao‐Min; Shen, Miao‐Miao; Kang, Jian; Luo, Yuan‐Long; Wang, Shu‐Wen
Abstract: Characterizing the spatial distribution of precipitation across the Tibetan Plateau (TP) is important for understanding how the topography and atmospheric circulation influence the climatic patterns of the region. We collected 143 surface soil samples from the central and southeastern TP (SETP) for rock magnetic characterization of the spatial distribution of the pedogenic intensity. Comparison with meteorological data shows that pedogenic intensity decreases significantly along the pathway of moist air across the SETP toward the interior, and that there is a positive correlation between pedogenic magnetite/maghemite content and mean annual precipitation. By contrast, the samples from the central TP show a low degree of pedogenic alteration, consistent with the limited precipitation within this area. The results indicate the possibility of using magnetic properties of surface soils to determine the precipitation distribution in areas lacking meteorological stations. These observations, combined with published soil magnetic results, help to define the climatic boundary in the TP. Plain Language Summary: Detailed information about the precipitation boundary across the Tibetan Plateau (TP) is lacking, which hinders our understanding of the dynamic relationships between precipitation distribution and atmospheric circulation patterns in this tectonically and climatically sensitive region. We used systematic environmental magnetic measurements of a large set of surface soil samples, combined with the analysis of a ∼ 70‐year meteorological data set to provide a comprehensive picture of the spatial distribution of precipitation in the TP and its adjacent areas. Additionally, a synthesis of all of the available magnetic data for surface samples clearly delineates the precipitation boundary between sub‐humid to semi‐arid and arid regions in the TP and its adjacent areas, providing important boundary conditions for regional climate modeling in the future. Key Points: A critical altitudinal threshold of maximum mean annual precipitation is observed at 3, 000–3, 200 m a.s.l. in the southeastern Tibetan Plateau (TP) Variations in magnetic properties of surface soils can be used to determine the precipitation distribution across the TP A precipitation boundary between sub‐humid to semi‐arid and arid regions across the TP is defined